1993
DOI: 10.1177/000331979304400203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging and Hematocrit on Cerebral Blood Flow Velocity in Patients with Unilateral Cerebral Infarctions: A Doppler Ultrasound Evaluation

Abstract: By means of conventional continuous-wave (CW) (4 MHz) and transcranial pulsed (2 MHz) Doppler sonography 50 patients (34 men and 16 women, mean age 58.6 +/- 7.6 years) who survived unilateral cerebral infarctions (UCI) in the middle cerebral artery (MCA) territory were investigated. The control group consisted of 30 presumed healthy age-matched persons. The main quantitative sonographic parameters of the major arteries of the head and the basal cerebral arteries were evaluated. On the day of the neurosonograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The cardiac function seems to has a direct influence on the left carotid blood flow, maintaining the showing that these risk factors worsen the carotid blood flow predominantly on the side of the cerebral infarction due to insufficient collateral circulation. Similar results were found in our previous studies using conventional CW [13] and transcranial Doppler sonography [11]. All these findings are in agreement with the hypothesis of Wood and Kee [15], who suggested that the reduction in cerebral blood flow secondary to increased BV associated with HT has an inverse effect on the collateral blood flow in patients with UCI.…”
Section: Discussionsupporting
confidence: 93%
“…The cardiac function seems to has a direct influence on the left carotid blood flow, maintaining the showing that these risk factors worsen the carotid blood flow predominantly on the side of the cerebral infarction due to insufficient collateral circulation. Similar results were found in our previous studies using conventional CW [13] and transcranial Doppler sonography [11]. All these findings are in agreement with the hypothesis of Wood and Kee [15], who suggested that the reduction in cerebral blood flow secondary to increased BV associated with HT has an inverse effect on the collateral blood flow in patients with UCI.…”
Section: Discussionsupporting
confidence: 93%
“…Of particular relevance to this study is the fact that prior studies have suggested that small arterial vessels are a significant determinant of vascular resistance. 16,17 Previous investigators have demonstrated an elevation in PIs with increasing age 18,19 and hypertension 20 and with the presence of vascular dementia. 21 In our study, both age and hypertension were strongly correlated with increasing PI on univariate analysis; however, in multivariate analysis, only age remained an independent predictor of higher PI.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies showed that PI increases in hyperlipidemia, hypertension,[ 14 ] diabetes,[ 15 ] increasing age,[ 16 ] and vascular dementia. [ 17 ] Some studies showed that another indexes in TCD not PI increase due to SVD.…”
Section: Discussionmentioning
confidence: 99%